Serum galactomannan assay for diagnosis of probable invasive Aspergillosis in acute leukemia and hematopoietic stem cell transplantation - Indranil Ghosh; Vinod Raina; Lalit Kumar; Atul Sharma; Sameer Bakhshi; Sobuhi Iqbal (Indian Journal of Medical and Paediatric Oncology)
Background: Invasive aspergillosis (IA) is a leading cause of mortality in acute leukemia and hematopoietic stem cell transplantation (HSCT). Aims: To determine the yield of galactomannan (GM) assay for the diagnosis of probable IA, its temporal relationship with the computed tomography (CT) scans and correlation with mortality in AL and HSCT. Patients and Methods: Consecutive neutropenic episodes (n=150) among inpatients aged ≥15 years with AL or recipients of HSCT were prospectively evaluated over 1΍ years. All patients underwent weekly serum GM assay and optical density index >0.5 for ≥2 samples was defined as positive. IA was diagnosed according to EORTC 2008 guidelines. Results: Of the 150 episodes enrolled, 43 (28.7%) were diagnosed with IA: possible 25 (16.7%), probable 17 (11.3%) and proven 1 (0.7%). The yield of GM assay in diagnosing probable IA was 17/42 (40.5%). In 88.2% of probable IA episodes, GM was positive before high-resolution CT at a median of 10 days (range 1-16). In the episodes with ≥2 samples tested, fatality was higher in those ≥2 values positive for GM, compared to the rest (31% vs. 13.2%, odd ratio 2.96, 95% CI 1.09-8.00; P=0.04). Conclusions: In AL and HSCT, GM assay could identify patients with probable IA earlier than CT chest and also predicted a higher risk of death.